Colloid Chemistry - José Luis Toca-Herrera (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue Colloid Chemistry presents a comprehensive overview of what opportunities the colloidal scale, i.e., the nanoscale, offers to scientists from chemistry, physics, materials sciences, and biomedicine. Sophistically designed colloids are used for studying physical and physicochemical phenomena to gain a deeper understanding of interparticle interactions, not forgetting that such insights can be used to create tailored materials for a variety of applications. This Issue covers aspects from the synthesis to the analysis of colloidal properties and presents opportunities for their further application.